1995
DOI: 10.21273/hortsci.30.4.788b
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methods to Transform Embyrogenic Cotyledons of Melon

Abstract: Agrobacterium-mediated transformation (AMT) was compared with a particle bombardment (PB) for stable transformation of `Eden Gem', a melon with high embryogenic potential. Pretreated cotyledonary explants were either wounded via particle bombardment prior to Agrobacterium infection or were bombarded with plasmid-coated gold microparticles, using a modified particle inflow-type gun. Although similar numbers of embryos initially were obtained with eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Comparing Agrobacteriunt. transformation and particle bombardement, Gonsalves et aL (1994) and Gray et al (1995) indicates that a similar percentage of transgenic shoots and embryos is obtained by both methods.…”
Section: Technique Of Transformationmentioning
confidence: 83%
See 1 more Smart Citation
“…Comparing Agrobacteriunt. transformation and particle bombardement, Gonsalves et aL (1994) and Gray et al (1995) indicates that a similar percentage of transgenic shoots and embryos is obtained by both methods.…”
Section: Technique Of Transformationmentioning
confidence: 83%
“…Particle gun transformation has been described by Gaba et aJ. (1992) and Gonsalves et al (1994) using organogenic explants and by Gray et al (1995) using embryogenic explants. Comparing Agrobacteriunt.…”
Section: Technique Of Transformationmentioning
confidence: 99%
“…Melon transformation has been successfully obtained with reporter genes (Fang and Grumet 1990;Gray et al 1995;Akasaka-Kennedy et al 2004) and several plant traits, such as virus resistance (Fang and Grumet 1993;Yoshioka et al 1993;Gonsalvez et al 1994;Fuchs et al 1997;Huttner et al 2001;Yalcin-Mendi et al 2004;Gaba et al 2004 ;Wu et al 2010), salt tolerance (Bordas et al 1997) and long fruit shelf life (Ayub et al 1996;Ezura et al 1997;Silva et al 2004;Curuk et al 2005;Papadopoulou et al 2005;Nunez-Palenius et al 2006) have been incorporated into different melon types or into other Cucurbitaceae (Han et al 2005;Ntui et al 2010). Transformation capacity varies widely according to the cultivar Comment citer ce document : Chovelon, V., Restier, V., Giovinazzo, N., Dogimont, C., Aarrouf, J.…”
Section: Introductionmentioning
confidence: 99%
“…Gaba et al [63] and Gonsalves et al [64] used particle gun bombardment to transform muskmelon explants and recover transgenic plants through organogenesis. Gray et al [65] used the same transformation protocol and recovered plants from embryogenic materials. Gonsalves et al [64] and Gray et al [65] reported both that A. tumefaciens and microprojectile gene transfer produced almost the same percentage of transgenic plants.…”
Section: Improvement Of Muskmelon Using Recombinant Technologymentioning
confidence: 99%
“…Gray et al [65] used the same transformation protocol and recovered plants from embryogenic materials. Gonsalves et al [64] and Gray et al [65] reported both that A. tumefaciens and microprojectile gene transfer produced almost the same percentage of transgenic plants. Transformation success via Agrobacterium or particle gun bombardement is genotype-, explant source-, and in vitro culture conditions-dependent [64][65][66][67][68][69][70][71][72][73].…”
Section: Improvement Of Muskmelon Using Recombinant Technologymentioning
confidence: 99%